2016
DOI: 10.1002/hep.28517
|View full text |Cite
|
Sign up to set email alerts
|

Human intrahepatic regulatory T cells are functional, require IL‐2 from effector cells for survival, and are susceptible to Fas ligand‐mediated apoptosis

Abstract: Regulatory T cells (Treg) suppress T effector cell proliferation and maintain immune homeostasis. Autoimmune liver diseases persist despite high frequencies of Treg in the liver, suggesting that the local hepatic microenvironment might affect Treg stability, survival, and function. We hypothesized that interactions between Treg and endothelial cells during recruitment and then with epithelial cells within the liver affect Treg stability, survival, and function. To model this, we explored the function of Treg a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 42 publications
5
94
0
Order By: Relevance
“…However, intrahepatic Treg from autoimmune and inflamed livers had mostly a non-exhausted memory phenotype, expressed more functional relevant surface markers than peripheral blood Treg, and were functional in in-vitro studies [13, 14, 26]. The demethylated TSDR of the FOXP3 gene characterizes stable and suppressive Treg [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, intrahepatic Treg from autoimmune and inflamed livers had mostly a non-exhausted memory phenotype, expressed more functional relevant surface markers than peripheral blood Treg, and were functional in in-vitro studies [13, 14, 26]. The demethylated TSDR of the FOXP3 gene characterizes stable and suppressive Treg [23].…”
Section: Discussionmentioning
confidence: 99%
“…We recently described intrahepatic Treg as predominantly effector memory lymphocytes with PD1 low , CD69 high phenotype (15) and expressing both hepatic homing CXCR3 and biliary tropic CCR6 chemokine receptors (14) (Figure 1). …”
Section: Profile Of Regulatory T Cells In Liver Diseasesmentioning
confidence: 99%
“…In this report, we analyzed the role of the immune regulator, CEACAM1, in a murine model of acute immune‐mediated liver injury and observed that it promotes IL‐2‐mediated signaling in CD4 + T cells, Treg induction, and Treg stability. The importance of IL‐2 for the survival and suppressive function of Tregs in patients with autoimmune liver diseases has been highlighted recently . Tregs constitutively express the high‐affinity receptor for IL‐2 (CD25; IL‐2Rα), which enables IL‐2 to control Treg homeostasis by STAT5‐mediated signaling .…”
Section: Discussionmentioning
confidence: 99%
“…Splenic single‐cell suspensions from ConA‐treated mice were either directly subjected to phosphorylated STAT5 (pSTAT5) labeling, or NPCs from livers were isolated and restimulated before pSTAT5 labeling in T cells . Detailed procedures for pSTAT5 labeling are described in Chen et al…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation